A Type-2 Fuzzy Sonewhere Dense Set In General Type-2 Fuzzy Topological Space - Hussan, Mohammed Salih Mahdy; AL-Khafaji, Munir Abdul Khalik (Iraqi Journal of Science, 2020)
The multiplicity of connotations in any paper does not mean that there is no main objective for that paper and certainly one of these papers is our research the main objective is to introduce a new connotation which is type-2 fuzzy somewhere dense set in general type-2 fuzzy topological space and its relationship with open sets of the connotation type-2 fuzzy set in the same space topology and theories of this connotation.